The Cambridge dictionary of Christianity - Patte, Daniel (Cambridge ; New York : Cambridge University Press, 2010)
Written by a team of 800 scholars and practitioners from around the world, the volume reflects the plurality of Christianity throughout its history. --from publisher description
Keywords: Christianity -- Dictionaries